Spatio-temporal evolution and influencing factors of the e-sports industry in China - Zhu, Yixin; Yang, Zhenshan; Cheng, Zhe (ERDKUNDE, 2024)
The emergence and development of new industry play a key role in regional development and economic growth. This study explores the e-sports industry evolution, a typical cross-sector new industry, through a theoretical lens of the evolutionary economic geography (EEG) based on Chinese e-sports industry enterprise data between 1998–2018 and examines the influencing factor by multivariate regression. Results show e-sports industry development is a typical evolutionary process that combines spin-off, path creation, spatial evolution, and firms’ network. Furthermore, the e-sports industry is characterized by the integration of the sports and creative industries. However, technology correlated-based knowledge spillover from culture and sports does not significantly impact the e-sports industry, whereas the knowledge spillover from the information software industry promotes e-sports industry development. The regression result also confirms that the institution and culture significantly impact the industrial development. This study enriches the knowledge body of evolutionary economic geography from case studies of the e-sports industry, and also expands the existing study system of emerging industries.